Sveobuhvatna analiza α i β-thalassemia genotipa i hematoloskih fenotipa: Analysis of thalassemia genotypes and hematologic phenotypes - Wang, Heng; Huang, Hai; Chen, Yaping; Xie, Dan; An, Bangquan; Huang, Shengwen (Journal of Medical Biochemistry, 2024)
Background: Guizhou Province is an area with high incidence of thalassemia. However, there are few large-sample studies on the correlation between genotypes and phenotypes in Guizhou Province. In this study, the phenotypes and genotypes of 1174 patients with thalassemia in Guizhou Province were collected, and the relationship between different genotypes and phenotypes was analyzed, providing a more accurate basis for genetic counseling, prevention and control of thalassemia. Methods: A total of 1174 patients with thalassemia were collected in Guizhou Provincial People’s Hospital from October 2020 to December 2021 by PCR-reverse dot blot (RDB) hybridization assay, and their red blood cell (RBC), hemoglobin (Hb), mean erythrocyte volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red blood cell distribution width (RDW), hemoglobin (HbA), hemoglobin A2(HbA2), and fetal hemoglobin (HbF) data were collected. The relationship between different genotypes and phenotypes was analyzed. Results: Among 1174 cases of thalassemia or carriers, there were 617 cases of α-thalassemia, 512 cases of β-thalassemia, 45 cases of coinheritance of α- and β-thalassemia. The severity of anemia between α-thalassemia was positively correlated with the decrease of non-functional copy number of α-globin gene. The degree of anemia in non-deletion α-thalassemia was greater than that in deletion α-thalassemia. In β-thalassemia, β0 gene mutation did not produce β-globin, and β+ mutation expressed some β-globin, but it was lower than normal level. β0/β0 had no β-globin production, and long-term blood transfusion was required to maintain life. Compared with α-thalassemia, the degree of anemia in β-thalassemia whose clinical type was same as α-thalassemia was more serious. The anemia degree of coinheritance of α- and β-thalassemia was less than that of simple α-thalassemia or β-thalassemia. Conclusion: The clinical phenotype of thalassemia is influenced by molecular mechanism, and the two kinds of thalassemia can interact with each other. The clinical severity is positively correlated with the imbalance of α peptide chain and β peptide chain. A comprehensive understanding of the hematologic phenotype differences between different genotypes and subtypes of thalassemia can provide more accurate data for genetic counseling of thalassemia.